SUBPOENA AS A FORM OF DEVELOPER'S LEGAL EFFORT TO CONSUMERS IN CANCELING PROPERTY RESERVATIONS - Putu Gede Wahyu Santika Pratama; I Wayan Novy Purwanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
This study aims to investigate whether subpoenas can serve as a legal recourse for developers in the cancellation of property reservations and to comprehend the process of issuing subpoenas to consumers for canceling property reservations in Badung Regency. The research methodology employed is empirical legal research without statutory approaches, relying on factual analysis. Primary information was gathered through interviews with respondents and informants, while secondary data sources included literature, journals, and internet legislation. Data collection techniques involved documentation studies, and analysis was conducted through descriptive analysis. The research findings indicate that subpoenas can be utilized as a legal remedy by developers for consumers canceling property orders. Subpoenas are issued by delivering appeals and warnings through familial and economic approaches regularly. This legal effort aims to prevent financial losses for developers in the Badung district resulting from consumer order cancellations.